Pseudomonas in Meat Processing Environments - Chloe Calhoun; Ifigenia Geornaras; Peipei Zhang (Foods)
Pseudomonas is often predominant and/or prevalent among the residential microbiota in food processing facilities and has the potential to enhance the survival of pathogenic bacteria in these environments. This review aims to discuss our current understanding of this bacterial genus in meat processing environments. We specifically focus on the predominant species of Pseudomonas in meat and meat processing plants, their biofilm-forming abilities and affecting factors, and the interaction between Pseudomonas and foodborne pathogens in biofilms. Published accounts indicate Pseudomonas has more diversity within and between meat plants compared to that in meat products. Despite the competition between Pseudomonas and other bacteria, including pathogens, this genus can increase the survival of pathogenic bacteria in food processing-related environments by increasing the resistance of pathogens to antimicrobials when present in biofilms. Our understanding of the ecology of Pseudomonas in meat processing environments needs further exploration. Future studies should consider biofilms formed under dynamic conditions simulating meat plant operations, using species/strains that are more representative of the Pseudomonas populations found in meat processing environments, and with growth media that closely resemble the nutrients found on meat processing surfaces.